Development and progress on hydrogen metallurgy - Tang, Jue; Chu, Man-sheng; Li, Feng; Feng, Cong; Liu, Zheng-gen; Zhou, Yu-sheng (International journal of minerals, metallurgy and materials, 2020)
Hydrogen metallurgy is a technology that applies hydrogen instead of carbon as a reduction agent to reduce CO 2 emission, and the use of hydrogen is beneficial to promoting the sustainable development of the steel industry. Hydrogen metallurgy has numerous applications, such as H 2 reduction ironmaking in Japan, ULCORED and hydrogen-based steelmaking in Europe; hydrogen flash ironmaking technology in the US; HYBRIT in the Nordics; Midrex H 2 ™ by Midrex Technologies, Inc. (United States); H 2 FUTURE by Voestalpine (Austria); and SAL-COS by Salzgitter AG (Germany). Hydrogen-rich blast furnaces (BFs) with COG injection are common in China. Running BFs have been industrially tested by AnSteel, XuSteel, and BenSteel. In a currently under construction pilot plant of a coal gasification-gas-based shaft furnace with an annual output of 10000 t direct reduction iron (DRI), a reducing gas composed of 57vol% H 2 and 38vol% CO is prepared via the Ende method. The life cycle of the coal gasification—gas-based shaft furnace—electric furnace short process (30wt% DRI + 70wt% scrap) is assessed with 1 t of molten steel as a functional unit. This plant has a total energy consumption per ton of steel of 263.67 kg standard coal and a CO 2 emission per ton of steel of 829.89 kg, which are superior to those of a traditional BF converter process. Considering domestic materials and fuels, hydrogen production and storage, and hydrogen reduction characteristics, we believe that a hydrogen-rich shaft furnace will be suitable in China. Hydrogen production and storage with an economic and large-scale industrialization will promote the further development of a full hydrogen shaft furnace.